Ascender. Volume one, The haunted galaxy - Lemire, Jeff; Nguyen, Dustin (Image Comics, 2019)
"Set 10 years after the conclusion of DESCENDER's storyline, here magic has taken the place of machinery and the rules are very different indeed... Mila, the daughter of Andy and Effie from DESCENDER, spends her days exploring the lonely wilds of the planet Sampson and trying to stay out of the clutches of the evil disciples of the all powerful vampire witch known only as Mother. But like her parents, Mila doesn't like to play by the rules and when a certain robot pal of her dad's shows up, nothing will ever be the same!"--Provided by publisher.